Publishing the “Unpublishable”: The making of Kurdish publishing in Turkey - Mülayim, Gökhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This thesis aims to explore the making of Kurdish publishing in Turkey by asking how that field emerged and has been developed under the conditions inimical to the use and reproduction of Kurdish literary language. My exploratory journey into that terrain focuses on both the diachronic development of the conditions of possibilities underlying its emergence and the synchronic dynamics characterizing its conditions of existence. Drawing on both the secondary data collected through archival research and the qualitative data collected through ethnographic one, I argue that Kurdish publishing is situated not simply at the intersection of culture and economy, but rather at the intersection of culture and politics as a form of cultural resistance. Rather than taking this form of resistance as a monolithic one, I use Bourdieu's conception of the field to frame the complexity of the dynamics constituting that form of resistance, and I define two moments characterizing the making of that field: struggle and competition. While the former moment denotes the relations of antagonism between the Kurdish publishers and the state, the market imperative and the predominant public perceptions, the latter one stands for the relations of agonism among the publishers making that field.
Keywords: Kurdish imprints -- Turkey -- History.; Kurdish language -- Readers.